Study of Molecular Docking, Molecular Dynamics, Pharmacokinetics and Toxicity Prediction: Compounds from Nigella sativa Linn, Andrographis paniculata Nees, and Propolis as Inhibitors of Mycobacterium tuberculosis Growth - Asarini; Abdillah, Syamsudin; Sani, Yulvian; Alam, Gemini (Basic and Applied Nursing Research Journal, 2024)
Background: Tuberculosis (TB) is caused by *Mycobacterium tuberculosis*, and Multiple Drug-Resistant Tuberculosis (MDR-TB) arises from resistance to first-line treatments like Rifampicin and Isoniazid. Since current TB medications have been used for over four decades, discovering new drug candidates is critical. This research focuses on herbal compounds—Black cumin (*Nigella sativa*), Sambiloto (*Andrographis paniculata*), and propolis—as potential inhibitors of *M. tuberculosis* by targeting DHFR. The objective of the study is to predict the activity of these herbal compounds prior to in vitro and in vivo testing. Methods: This study employed computational tools, including Molegro Virtual Docking (MVD) and Molecular Dynamics (MD), to assess the interactions of the herbal compounds with DHFR (PDB ID: 2CIG). Pharmacokinetic predictions were also conducted to evaluate the absorption and toxicity of the compounds. Results: Molecular docking and MD simulations indicated that Andrographolide, Thymoquinone, and Caffeic Acid Phenethyl Ester effectively inhibited the growth of *M. tuberculosis*. The analysis revealed favorable binding interactions and conformational changes in DHFR, with significant activity observed for Thymoquinone. Conclusion: This study suggests that Andrographolide, Thymoquinone, and Caffeic Acid Phenethyl Ester may serve as promising candidates for further development as anti-tuberculosis drugs. Subsequent in vitro and in vivo studies are warranted to validate their therapeutic potential.